Cell lineage of primary and secondary enamel knots - Matalova, E; Antonarakis, G S; Sharpe, P T; Tucker, A S (Developmental dynamics, 2005)
Recent research indicates that control of cusp morphology involves a signalling center at the heart of the developing tooth germ, known as the enamel knot. The primary enamel knot forms in both incisors and molar tooth germs at the cap stage of tooth development. Secondary and tertiary enamel knots only develop in molar tooth germs. These sit at the sites of future cusp tips from the early bell stage of tooth development. In studies describing the relationship between the primary and secondary enamel knots, it is often assumed that there is a cellular continuity between these structures, such that cells from the primary enamel knot physically contribute to the secondary enamel knots. We have devised a method whereby the developing tooth germ can be cultured in frontal slices with the enamel knot visible. The fate of the primary enamel knot cells can then be followed by 1,1', di-octadecyl-3,3,3',3',-tetramethylindo-carbocyanine perchlorate (DiI) labeling. Using this method, no cells of the primary enamel knot were seen to move toward the developing secondary enamel knots. Thus, although the primary and secondary enamel knots have a close molecular and functional relationship in molar development, they are not actually derived from the same cells.
Keywords: Dental Enamel; Cell Lineage; myši; Animals; Tooth Germ; karbocyaniny; Tissue Culture Techniques; buněčný rodokmen; Mice; zvířata; techniky tkáňových kultur; zubní zárodek; Carbocyanines; zubní sklovina